Types of parent-child relationship and indicators of neuropsychological development of preschool children - Ekaterina Ermolova; Olga Shamshikova (Mental Health: Global Challenges Journal, 2020)
Introduction: During the last 20 years, in Russia and in many EU countries, there has been significant change in the global social and cultural situation.  Individualistic tendencies rose sharply and there is a widespread destruction of the sense of belonging.  In this regard, the type of parent-child relationship is changing, which is one of the key dimension of the neuropsychological development of children.  There is a logical question for psychologists, teachers and parents, what types of parent-child relationships are constructive, that is, they favor normal neuropsychological development of children of preschool age (6-7 years).